Transformation of agricultural and undeveloped land in the Boland region of the Western Cape - Niemand, Bernard (Barend Jakobus Petrus) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2011.